Impact of Tourism Sector on the GDP Growth of Developing and Developed Countries - Ameenullah Aman; Syed Muhammad Umer (Social Science Review Archives, 2025)
This research is basically focused to find the impact of tourism industry on the GDP or economic growth of developed countries and also on the economic growth of developing countries. We have selected four major factors or variables of tourism sector of both developing and developed countries and on the basis of these factors we are studying the tourism sector of these countries and trying to figure out what is their effect on GDP or economic growth of developing and developed countries. We have used panel data analysis to conduct our research. We have selected 10 developing and 10 developed countries in different models from the time period of 2010 to 2023. The results of the study of developing countries shows that tourism expenditures, tourism receipts and tourism expenditures % of total imports has significant impact on GDP and number of tourist arrivals has insignificant effect on GDP. While the results of the study of developed countries shows that tourism expenditures and tourism receipts has significant effect on GDP while tourism expenditures % of total imports and number of tourist arrivals has insignificant impact on GDP growth. Based on this research government of these countries can focus on these major variables or factors of tourism to enhance the performance of their tourism industry that can have positive impact on GDP growth of these countries.